I1171 missense mutation (particularly I1171N) is a common resistance mutation in ALK-positive NSCLC patients who have progressive disease while on alectinib and is sensitive to ceritinib. Issue 2 (May 2015) - Ou, Sai-Hong Ignatius; Greenbowe, Joel; Khan, Ziad U.; Azada, Michele C.; Ross, Jeffrey S.; Stevens, Phil J.; Ali, Siraj M.; Miller, Vincent A.; Gitlitz, Barbara
Abstract Objectives Acquired resistance mutations to anaplastic lymphoma kinase (ALK) inhibitors such as crizotinib and alectinib have been documented in non-small cell lung cancer (NSCLC) patients harboring ALK rearrangement (ALK+). Of note I1171T/N/S mutations in the ALK kinase domain have recently been described by several groups to confer resistance to alectinib, a second-generation ALK inhibitor. Additionally one of these reports demonstrated one ALK+ NSCLC patient harboring an I1171T acquired mutation has responded to ceritinib, another second-generation ALK inhibitor. Materials and methods We reported the presence of an ALK I1171N resistance mutation from comprehensive genomic profiling from a liver biopsy of a progressing metastatic lesion in an ALK+ patient on alectinib after an initial partial response. The patient then responded to ceritinib 750 mg orally once daily but required dose reduction to 600 mg once daily. She initially had grade 3 elevation of liver enzymes from crizotinib necessitating the original switch to alectinib but experienced no transaminase elevations with alectinib or ceritinib. Conclusions This is the fifth patient case to date demonstrating that ALK I1171 mutation confers resistance to alectinib and the second reported case of ALK I1171 mutation being sensitivity to ceritinib. Substitutions of isoleucine at amino acid 1171 in the ALK kinase domain may distinguish which second generation ALK inhibitor will be effective after crizotinib failure. This case also provides evidence that transaminase elevations is likely a unique adverse event associated with crizotinib and unlikely a "class" effect involving all ALK inhibitors.